Jabir Ibn Hayyan's work on sulphur-mercury theory - Rosli, Adib Hamdani; Shafie, Amir Akramin (IIUM Press, 2011)
The objectives of this chapter are to explain origin of sulphur-mercury theory proposed by Jabir ibn Hayyan, a Muslim alchemist as well as its contribution -directly and indirectly, to the alchemy and later, modern chemistry world. The significance of this chapter is its ability to highlight the importance of sulphur-mercury theory during middleages in alchemical field of study, as well as how the theory became the basis for several theories in chemistry centuries later, namely acid-base theory and terra pinguis concept. The methods used in this chapter are collection of academic references in terms of books and journals, as well as reliable online references. The chapter framework covers the origin of sulphur-mercury theory -which is dated back to the time of Aristotle, and the importance or contribution of the theory to alchemical as well as chemistry fields.